Early Japanese art : - Kidder, J. Edward (Van Nostrand, 1964)
The Art of Japanese Architecture explores the simplicity, asymmetry, sensitivity to the natural environment, and use of natural materials that are the hallmarks of Japanese architecture. These elements are explored and clarified in this cultural and historical overview of the rapidly changing world of Japanese architecture